When Less Is More: Investigating Factors Influencing the Distraction Effect of Virtual Reality From Pain - Barcatta, Katharina; Holl, Elisabeth; Battistutta, Layla; van der Meulen, Marian; Rischer, Katharina M. (Frontiers in Pain Research, 2022)
Virtual reality (VR) is a powerful method of redirecting attention away from pain. Yet, little is known about which factors modulate the size of this distraction effect. The aim of this study was to investigate the role of cognitive load and inter-individual differences in the cognitive and affective domain on heat pain thresholds during a VR game. Ninety healthy participants (mean age ± SD: 23.46 ± 3.28; 50% identified as male and 50% as female) played a low and high load version of a VR game while heat pain thresholds and heart rate were recorded. The effects of cognitive load were assessed by computing the difference in pain thresholds between the high and low load condition for each participant. In addition, we computed the difference in heart rate variability (HRV) measures between both conditions to explore whether these would be correlated with the difference in heat pain thresholds. Prior to the VR session, participants completed questionnaires about their emotional distress, pain-related cognitions, and different executive functioning tasks. Contrary to our expectations, not all participants benefitted from a higher load in terms of distraction from pain. Logistic regression analysis revealed that participants who reported more emotional distress were more likely to exhibit higher pain thresholds in the low relative to the high load condition. Accordingly, these participants tended to show marginally higher HRV in the low compared to the high load condition. Our study demonstrates that the potential benefits of an increased cognitive load in VR on pain sensitivity depends on individual differences in affective state.